Analysis of the Factors Contributing to the Shortage Teacher Ratio in Rural Public Elementary Schools - Mulyani, Jajang Dede; Festiawan, Rifqi; Aryani, Aisyah Apriliciciliana; Agus, Herdiansyah (TEGAR: Journal of Teaching Physical Education in Elementary School, 2024)
This study aims to analyze the factors contributing to the low teacher ratio in public elementary schools in Banyumas Regency, understand the potential risks if this issue is not addressed, and propose solutions. The research employs a qualitative study with an exploratory descriptive design, involving in-depth interviews with school principals, data triangulation with teachers and the Banyumas Regency Education Office, and data analysis using NVivo 14 software for visualization and analysis. The findings indicate that geographical location of schools, adaptation to new cultures, and policies play significant roles in the low teacher ratio in rural schools. The risks associated include a decline in education quality, increased workload for teachers, and negative impacts on student quality. Solutions implemented include the recruitment and transfer of teachers, as well as improvements in infrastructure and facilities. Collaboration between the government, schools, and local communities is necessary, along with the implementation of policies that support a more equitable and fair distribution of teachers.